On the role of AEBP2 in thymus development and function - Wu, W (2019)
The ability to distinguish between “Self” and “Non-Self” constitutes the most important functional feature of the immune system. It is primarily instructed for T cells by thymic epithelial cells (TECs) and is made possible by the TEC’s unique capacity to transcribe at the population level nearly all protein coding genes. This expertise, known as promiscuous gene expression (PGE), is in part dependent on the presence of the transcriptional facilitator, Autoimmune Regulator (AIRE) in a subpopulation of medullary TEC (mTEC).